1995
DOI: 10.1177/036354659502300202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Evaluation of the Rotator Cuff Tendons in the Asymptomatic Shoulder

Abstract: Thirty shoulders in 20 volunteers (average age, 29 years; range, 17 to 49) with no shoulder symptoms or known abnormalities were scanned using magnetic resonance imaging. All scans were interpreted by one radiologist who was blinded to clinical data. Appearance of rotator cuff tendons on the images was graded. Grade 0 was normal, homogeneous low signal intensity structure. Grade 1 lesion was focal, linear, or diffuse intermediate signal through the tendon. Grade 2 lesion was high signal intensity within the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 10 publications
4
49
1
4
Order By: Relevance
“…We observed that the prevalence of asymptomatic rotator cuff tears increased with age as has been reported in previous studies [5][6][7][8][9]17 . The prevalence of rotator cuff tears in asymptomatic subjects in this study is slightly lower than that reported by some investigators.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We observed that the prevalence of asymptomatic rotator cuff tears increased with age as has been reported in previous studies [5][6][7][8][9]17 . The prevalence of rotator cuff tears in asymptomatic subjects in this study is slightly lower than that reported by some investigators.…”
supporting
confidence: 85%
“…No imaging modalities were used to exclude asymptomatic rotator cuff tears in these studies. Rotator cuff tears are often asymptomatic in elderly individuals [5][6][7][8][9] . The prevalence of rotator cuff tears has been reported to be as high as 50% in asymptomatic individuals older than sixty years and may increase to 80% in those older than eighty years 5 .…”
mentioning
confidence: 99%
“…15,24,32 A vast majority of individuals with RCTs present with symptoms. 15,16,19,24,32 Failure of the rotator cuff tendon is the most common clinical problem of the shoulder in the elderly population, accounting for more than 4.5 million physician visits per year in the United States. 13,21 The natural history of degenerative cuff tendon failure is one of age-related progression.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…8 Ultrasonography is valuable for detecting full thickness tears, but less so for small tears. 8,19,21 Furthermore, asymptomatic tears are common, 16,18 so that lesions correctly diagnosed by imaging modalities are of uncertain significance.…”
Section: Discussionmentioning
confidence: 99%